The core structure of 60° mixed basal dislocation in alumina (α-Al2O3) introduced by in situ TEM nanoindentation. (1st April 2019) - Miao, Bin; Kondo, Shun; Tochigi, Eita; Wei, Jiake; Feng, Bin; Shibata, Naoya; Ikuhara, Yuichi
Abstract: The dislocation associated with the (0001)1/3< 11 2 ¯ 0> basal slip in alumina plays an important role on its plastic deformation at elevated temperatures. A 60° mixed basal dislocation was preferentially introduced by in situ transmission electron microscopy (TEM) nanoindentation, and characterized by atomic-resolution scanning TEM (STEM). It was revealed that the 60° mixed basal dislocation dissociates into two partial dislocations via self-climb with a stacking fault on the 1 1 ¯ 00 plane. The dissociation mechanisms of the basal dislocation have been discussed in terms of its core structure and atomic diffusion process. Graphical abstract: A 60° mixed basal dislocation was preferentially introduced and revealed to dissociate into two partials via self-climb process with the formation of stacking fault (SF) on the 1 1 ¯ 00 plane. The climb dissociation mechanisms of the basal dislocation were discussed based on its core structure and atomic diffusion process.Unlabelled Image